(untitled) (CIPEEX, 2026)
Objective: To compare the influence of fixed-bearing versus rotating-platform knee prostheses on pain and function outcomes, assessed with the WOMAC and GLFS-10-P questionnaires, in patients undergoing total knee arthroplasty (TKA). Methods: This study was conducted at a public hospital in Goiânia, Goiás, Brazil, with 37 patients with advanced osteoarthritis who underwent unilateral TKA, allocated to a fixed-bearing group (n = 19) or a rotating-platform group (n = 18). Two years after surgery, WOMAC and GLFS-10-P were administered in interview format. Descriptive statistics, confidence intervals, effect size (Cohen’s d), multiple linear regression (adjusting for age, sex, and postoperative time), and ROC curve analysis were used. The study was approved by the Research Ethics Committee (CAAE: 52052421.9.0000.5076). Results: No statistically significant differences were found between fixed-bearing and rotating-platform implants in total WOMAC scores (6.63 ± 7.30 vs. 5.22 ± 4.21, respectively) or GLFS-10-P scores (6.00 ± 4.70 vs. 6.83 ± 2.64). Multiple linear regression confirmed that implant type did not significantly influence functional outcomes after adjustment for covariates (p = 0.640). ROC analysis showed that the GLFS-10-P is a good predictor of higher WOMAC scores (AUC = 0.794), with an optimal cutoff of ≥ 6 (sensitivity 77.3%; specificity 73.3%). Conclusion: In this study, there was no clinical or statistical evidence of superiority between fixed-bearing and rotating-platform prostheses regarding pain and function. The GLFS-10-P proved to be a valid screening tool for identifying patients with greater postoperative dysfunction. Keywords: Knee arthroplasty; Nociceptive pain; Orthopedics.